2016
DOI: 10.5194/isprs-archives-xli-b4-125-2016
|View full text |Cite
|
Sign up to set email alerts
|

Nasadem Global Elevation Model: Methods and Progress

Abstract: ABSTRACT:NASADEM is a near-global elevation model that is being produced primarily by completely reprocessing the Shuttle Radar Topography Mission (SRTM) radar data and then merging it with refined ASTER GDEM elevations. The new and improved SRTM elevations in NASADEM result from better vertical control of each SRTM data swath via reference to ICESat elevations and from SRTM void reductions using advanced interferometric unwrapping algorithms. Remnant voids will be filled primarily by GDEM3, but with reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 6 publications
0
68
0
Order By: Relevance
“…re-processing of the original data in the new NASADEM product, many of these errors remain (Crippen et al, 2016). On the other hand, the newer TanDEM-X apparently has far fewer biases related to satellite geometry, and most error is restricted to terrain characteristics like slope and vegetation, though results are still nascent (e.g., Baade and Schmullius, 2016;Purinton and Bookhagen, 2017;Wessel et al, 2018).…”
Section: Necessity Of Correction Stepsmentioning
confidence: 99%
See 4 more Smart Citations
“…re-processing of the original data in the new NASADEM product, many of these errors remain (Crippen et al, 2016). On the other hand, the newer TanDEM-X apparently has far fewer biases related to satellite geometry, and most error is restricted to terrain characteristics like slope and vegetation, though results are still nascent (e.g., Baade and Schmullius, 2016;Purinton and Bookhagen, 2017;Wessel et al, 2018).…”
Section: Necessity Of Correction Stepsmentioning
confidence: 99%
“…The SRTM-C has seen numerous succeeding releases and void filling (e.g., Jarvis et al, 2008). We use the most recent floating point re-processed 1 arcsec (~30 m) NASADEM, taking only the non-void filled original SRTM-C 20 tiles (herein SRTM-C; Crippen et al (2016); found in the "srtmOnly" directories under: https://e4ftl01.cr.usgs.gov/provisional/ MEaSUREs/NASADEM/). The TanDEM-X 0.4 arcsec (~12 m) DEM released in 2016-here received through scientific DLR proposals, though now available strictly commercially-is the next generation of radar-derived global topography following the SRTM.…”
mentioning
confidence: 99%
See 3 more Smart Citations